Efektivitas dan Keamanan Pretreatment Inhibitor P2Y12 Dibandingkan Tanpa Pretreatment pada Pasien dengan Sindrom Koroner Akut Non-Elevasi Segmen ST (NSTE-ACS) yang Menjalani Angiografi Koroner Invasif: Sebuah Tinjauan Sistematis: Effectiveness and Safety of P2Y12 Inhibitor Pretreatment Versus No Pretreatment in Patients With Non–ST-Elevation Acute Coronary Syndromes (NSTE-ACS) Undergoing Invasive Coronary Angiography: A Systematic Review - Setiawan, Anugrah Puspitasari; Kurnia, Jodii Arlan (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
The role of routine P2Y12 inhibitor pretreatment before invasive coronary angiography in non–ST-elevation acute coronary syndromes (NSTE-ACS) remains controversial. While early platelet inhibition may theoretically reduce ischemic complications, contemporary invasive strategies and more potent agents raise concerns about excess bleeding when coronary anatomy and revascularization plans are still unknown. A PRISMA guided systematic review was conducted, including randomized controlled trials and prespecified or post hoc analyses evaluating P2Y12 inhibitor pretreatment versus no pretreatment (or deferred initiation after angiography) in adult patients with NSTE-ACS undergoing an invasive strategy. Searches were conducted in PubMed, the Cochrane Library, and ClinicalTrials.gov. Outcomes included major adverse cardiovascular events (MACE), myocardial infarction, all-cause mortality, and major bleeding. Risk of bias was assessed using Cochrane RoB 2. Findings were synthesized narratively due to clinical and methodological heterogeneity. Six studies met inclusion criteria. Five studies directly compared pretreatment versus no pretreatment, primarily driven by the ACCOAST trial and related analyses, and the DUBIUS trial. Across direct comparisons, pretreatment did not reduce ischemic outcomes (MACE, myocardial infarction, or all-cause mortality) but was consistently associated with higher major bleeding risk (TIMI or BARC definitions), including in clinically relevant subgroups such as patients undergoing PCI. Analyses of pretreatment timing did not demonstrate ischemic benefit even with longer intervals before angiography. In invasively managed NSTE-ACS, routine P2Y12 inhibitor pretreatment does not improve ischemic outcomes and increases major bleeding. Evidence supports deferring P2Y12 initiation until coronary anatomy is defined and a revascularization strategy is clear, favoring a selective, individualized approach.